Fine Tuning Muscarinic Acetylcholine Receptor Signaling Through Allostery and Bias - van der Westhuizen, Emma T.; Choy, K. H. Christopher; Valant, Celine; McKenzie-Nickson, Simon; Bradley, Sophie J.; Tobin, Andrew B.; Sexton, Patrick M.; Christopoulos, Arthur (Frontiers in Pharmacology, 2021)
The M1 and M4 muscarinic acetylcholine receptors (mAChRs) are highly pursued drug targets for neurological diseases, in particular for Alzheimer's disease and schizophrenia. Due to high sequence homology, selective targeting of any of the M1-M5 mAChRs through the endogenous ligand binding site has been notoriously difficult to achieve. With the discovery of highly subtype selective mAChR positive allosteric modulators in the new millennium, selectivity through targeting an allosteric binding site has opened new avenues for drug discovery programs. However, some hurdles remain to be overcome for these promising new drug candidates to progress into the clinic. One challenge is the potential for on-target side effects, such as for the M1 mAChR where over-activation of the receptor by orthosteric or allosteric ligands can be detrimental. Therefore, in addition to receptor subtype selectivity, a drug candidate may need to exhibit a biased signalling profile to avoid such on-target adverse effects. Indeed, recent studies in mice suggest that allosteric modulators for M1 mAChR that bias signalling towards specific pathways may be therapeutically important. This review brings together details on the signalling pathways activated by the M1 and M4 mAChRs, evidence of biased agonism at these receptors, and highlights pathways that may be important for developing new subtype selective allosteric ligands to achieve therapeutic benefit.